Effects of Triptolide on the Pharmacokinetics of Cyclophosphamide in Rats： A Possible Role of CytochromeP3A4 Inhibition - 张细凤 刘炬 叶峰 姬森国 张妮 曹儒森 何玲 吴江川 李兴福 (Chinese journal of integrative medicine, 2014)
Objective： To evaluate the effect of a 10-day course of triptolide （TP） on rat cytochrome （CY） P3A4 activity, and on the pharmacokinetics of cyclophosphamide （CPA）. Methods： In the pharmacokinetics experiment, rats were orally given 0.9% NaCI solution （n=5） and TP [1.2 （mg/kg.d）] for 10 days and a single dose of CPA was administered intravenously （100 mg/kg） to rats on day 11. Blood samples were collected up to 4 h at predetermined time intervals, the plasma concentration of CPA was determined by high performance liquid chromatography （HPLC） and pharmacokinetic parameters were determined. In the in vitro CYP3A4 activity inhibition research, rat blank liver microsomes were divided into 3 groups： a control group, a TS （5μL, 200 μmol/L） with TP （5 μL, 12.5 μmol/L） group, a TS with ketoconazole （5 μL, 1 μmol/L） group. Concentration of 613 -hydroxylated testosterone （6β -OHT） in liver microsomes was measured by HPLC and the activity of CYP 3A4 was calculated through the following formula： Einhlbltot//Eoontrol×100%=Cinhlbltor/Ccontrol×100%. Results： Compared with the control group, the area under the plasma concentration-time curve （AUC0.∞） of CPA was significantly increased by 229.05% pretreated with TP （P〈0.01）. Peak plasma concentrations （Cmax of CPA was significantly increased and plasma half-life was correspondingly extended. The CYP3A4 activity was significantly inhibited by ketoconazole 93.5%± 0.2% and TP 84.6% ± 0.3% compared with the control group （P〈0.01 and P〈0.05, respectively）. Conclusion： Our results strongly suggested that long-term oral intake of TP can distinctly inhibit the CYP3A4 activity and this inhibition evidently decrease the formation of toxic metabolites of CPA.